Sol-Gel Synthesis, Characterization and Catalytic Activity of Pd Supported on Silica and Siloxane-Modified Silica - Mahmoud, S.S.; Arafa, I.M.; Sheikha, O.I. (Asian Journal of Chemistry, 2010)
Palladium supported on silica, Pd-SiO2, and on siloxanemodified silica, Pd-(CH3)2SiO·SiO2, were synthesized by sol-gel method. They were characterized by infrared spectroscopy X-ray diffraction spectrometry, magnetic susceptibility and BET surface area measurements. XRD confirmed that metallic Pd on the siloxane-modifIed silica and on silica supports adopted face. centered cubic structure. IR data of the modified system indIcated that the intensity of hydroxyl stretching band due to silanol moiety and water was dramatically decreased, and the methyl group is structurally intact. The BET surface area measurements showed that the surface area of the modifIed silica system is smaller than that of the silica system. In the liquid-phase hydrogenation of phenylacetylene over Pd/SiO2 and Pd/(CH3)2SiO2·SiO2 systems, Pd/SiO2 catalysts exhibited higher catalytic actiivity than the modified silica catalysts.